2023
DOI: 10.3389/fphar.2023.1135180
|View full text |Cite
|
Sign up to set email alerts
|

Effect of traditional Chinese medicine monomers interfering with quorum-sensing on virulence factors of extensively drug-resistant Acinetobacter baumannii

Abstract: The antimicrobial resistance of Acinetobacter baumannii (A. baumannii) clinical isolates has emerged as a great threat to public health. Quorum sensing (QS) is one of the resistance mechanisms for drug-resistant A. baumannii. Interfering with QS is a promising strategy to combat infections caused by drug-resistant bacteria. This study explored the QS inhibition ability of thirty-four traditional Chinese medicine monomers (TCMMs) and assessed the effect of QS inhibitors (QSIs) on the virulence factors of twelve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Nine traditional Chinese medicine monomers (TCMMs), such as caffeic acid, cinnamic acid, and vanillin, have exhibited QS inhibitory activity, thereby hindering biofilm formation and diminishing virulence. 43 In this study, treatment with tryptanthrin led to a reduction in the expression of the abaI/abaR gene. The two-component system (TCS) is a microbial signaling mechanism that enables the perception of and adaptation to changing environmental conditions.…”
Section: Discussionmentioning
confidence: 59%
“…Nine traditional Chinese medicine monomers (TCMMs), such as caffeic acid, cinnamic acid, and vanillin, have exhibited QS inhibitory activity, thereby hindering biofilm formation and diminishing virulence. 43 In this study, treatment with tryptanthrin led to a reduction in the expression of the abaI/abaR gene. The two-component system (TCS) is a microbial signaling mechanism that enables the perception of and adaptation to changing environmental conditions.…”
Section: Discussionmentioning
confidence: 59%
“…Unclear Inhibition of the QS system; the specific mechanism awaits further research Inhibition of adhesion and biofilm formation, and downregulation of the expression levels of virulence-associated genes [91] Traditional Chinese medicine Tanreqing (TRQ) formula Inhibition of upstream regulators of QS systems, including two-component systems GacS/GacA and PprA/PprB Inhibition of virulence factors [92] QSIs, quorum sensing inhibitors; AHL, acylated homoserine lactone; AI, autoinducer; AIP, autoinducing peptide; PQS, Pseudomonas quinolone signal.…”
Section: Acinetobacter Baumanniimentioning
confidence: 99%
“…The components of Chinese herbal medicines are extremely complex, and the extraction and separation of their active antimicrobial ingredients can improve the efficiency of mildew inhibitors [ 13 , 14 , 15 , 16 ]. Some Chinese herbal medicines have identified antimicrobial monomers [ 17 , 18 , 19 ] and determined their chemical structures [ 20 , 21 , 22 , 23 ]. It has been reported that among Chinese herbal antimicrobial substances, phenolic compounds exhibit the strongest antimicrobial activity, followed by aldehydes, alcohols, ketones, esters, and hydrocarbons [ 24 ].…”
Section: Introductionmentioning
confidence: 99%